APPLICATION D’ÉVALUATIONS D’EXPERTS POUR DÉTERMINER L’EFFICACITÉ DE L’UTILISATION DU POTENTIEL DE MAIN-D’ŒUVRE DES ENTREPRISES - BUKHALO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to study the methodology of expert assessment of labor potential of agricultural enterprises and determine the directions of its development in modern conditions of the socio-economic state. It is proved that the efficiency of the enterprises depends on their resource potential, including labor. The current socio-economic state of agricultural enterprises tends to deteriorate, this is due to both objective and subjective reasons. The need to conduct an expert assessment of labor potential when planning the further development of agricultural enterprises is a prerequisite for increasing production efficiency. The need for research was caused by a number of factors, including: a significant decrease in the population, a decrease in the efficiency of enterprises, and a loss of the level of personnel qualifications. In the context of modern challenges, it is appropriate to involve methods of simulation modeling and expert assessment of the production activities of enterprises, especially the use of their labor potential. The article summarizes proposals for reforming the labor resource management system, as well as the system of training and retraining of employees of agricultural enterprises. At the same time, there is a need to take into account domestic and foreign experience regarding the return on labor potential involved in the production of products.